Pengaruh Modal Usaha, Tenaga Kerja dan Pendidikan Terhadap Pendapatan Pelaku UMKM Rumah Makan/Restoran di Kabupaten Solok - Rizki Ramadhan; Jean Elikal Marna (Jurnal Ecogen, 2025)
This study aims to analyze the influence of business capital, labor, and education on the income of MSMEs operating in restaurants in Solok Regency. The population in this study was all MSMEs operating in the restaurant sector in Solok Regency. The sampling technique used was purposive sampling with a sample of 40 respondents. The sampling criteria were MSMEs operating in the restaurant sector that had been established for more than three years in Solok Regency. Data processing used SPSS version 24 software, with descriptive analysis, classical assumption analysis, multiple linear regression analysis, and hypothesis testing. The results showed that business capital, labor,  and education significantly and positively influenced the income of MSMEs operating in Solok Regency.